Determination of butoxyacetic acid (biomarker of ethylene glycol monobutyl ether exposure) in human urine candidate reference material - Šperlingová, Ilona; Dabrowská, Ludmila; Stránský, Vladimír; Dušková, Šárka; Kučera, Jan; Tvrdíková, Monika; Tichý, Miloň (Analytical and bioanalytical chemistry, 2010)
Ethylene glycol monobutyl ether (EGBE), an industrial solvent, is absorbed by the body not only by inhalation but also by dermal absorption (liquid or vapour). EGBE is metabolized to butoxyacetic acid (BAA). Pooled freeze-dried urine candidate reference material (RM) was prepared from urine obtained from persons occupationally exposed to EGBE. This material has the advantage of containing butoxyacetic acid in both the free and conjugated (glutamine and glycine) forms, as found in native urine. In all GC method modifications used, acid hydrolysis was used to release BAA from its conjugated form. The amount of butoxyacetic acid in homogeneity and stability testing was measured by GC after derivatisation with N-tert-butyldimethylsilyl-N-methyltrifluoroacetamide. Detection was by MS in EI mode, in the authors' laboratory. For interlaboratory comparison of the reference material GC methods with MS, FID, and ECD were used. Different extraction solvents (dichloromethane-isopropanol 2:1, ethyl acetate, or dichloromethane) and derivatisation reagents (trimethylsilyldiazomethane, N-tert-butyldimethylsilyl-N-methyltrifluoroacetamide) were used. Using ANOVA (at the statistical level alpha = 0.05) no changes were found in the concentration of butoxyacetic acid during fifteen month isochronous stability testing, or in homogeneity testing. The uncertainty contributions were u (h) = 8.8 mg L(-1) and u (s) = 6.5 mg L(-1). The concentration of butoxyacetic acid in freeze-dried urine RM was evaluated from the results of eight laboratory data sets within an interlaboratory comparison by use of the interactive statistical software IPECA. The contribution to total uncertainty derived from interlaboratory comparison was u (i) = 12.7 mg L(-1). The reference value (c = 273 +/- 33 mg L(-1)) is an unweighted arithmetic average of accepted results. The value is traceable to the pure butoxyacetic acid (98% w/w; Acros Organic #257760010) used as calibrant. The uncertainty given is combined expanded uncertainty derived from the results from interlaboratory comparison, and from homogeneity and stability tests (k = 2). The reference material will be used to verify method performance in the biological monitoring of occupational exposure to EGBE.
Keywords: Occupational Exposure; Gas Chromatography-Mass Spectrometry; Reference Standards; pracovní expozice; plynová chromatografie s hmotnostně spektrometrickou detekcí; ethylenglykoly; glykoláty; lidé; Glycolates; Ethylene Glycols; Humans; referenční standardy